Investigation of the relationship between the PaO₂/FiO₂ ratio and Wells score in patients diagnosed with acute pulmonary embolism (Annals of Medical Research, 2023)
Aim: In order to make a definitive diagnosis of acute pulmonary embolism (APE), patients to undergo computed tomography angiography (CTA) are selected according to certain criteria. This study aimed to examine the partial oxygen pressure PaO₂/inspired oxygen concentration ratio (P/F) as a new parameter to be used for this purpose in addition to the Wells score, which is one of the methods of determining clinical probability.Materials and Methods: This study was prospectively conducted between July 1, 2022, and October 1, 2022, and included 80 patients that presented to the emergency department with acute dyspnea and were diagnosed with APE using CTA. The Wells scores of the patients were recorded at the time of their presentation to the emergency department. IBM SPSS v. 20.0 was used for the statistical analysis of the data.Results: Of the cases included in the study, seven had a low probability, 57 had an intermediate probability, and 16 had a high probability of APE. The PaO₂ values of the patients were 56.7±8.0, 56.1±11.2, and 51.8±9.9 mmHg for the low, intermediate, and high probability groups, respectively. According to the Wells scores, the P/F ratios of the patients with low, intermediate, and high probability were determined as 205.5±72.2, 198.5±62.5, and 183.5±43.6, respectively.Conclusion: There was a negative correlation between the P/F ratio and Wells score, but this was not statistically significant. Therefore, it may not be appropriate to evaluate the P/F ratio in making a decision to perform CTA in clinical practice.
Keywords: Acute pulmonary embolism; Clinical decision-making rules; Hypoxia; P/f ratio; Pao₂/fio₂ ratio; Wells criteria